Iron, copper and silver nanoparticles: Green synthesis using green and black tea leaves extracts and evaluation of antibacterial, antifungal and aflatoxin B1 adsorption activity. (April 2018) - Asghar, Muhammad Asif; Zahir, Erum; Shahid, Syed Muhammad; Khan, Muhammad Naseem; Asghar, Muhammad Arif; Iqbal, Javed; Walker, Gavin
Abstract: The present study was aimed to account an eco-friendly synthesis of iron (Fe), copper (Cu) and silver (Ag) nanoparticles (NPs) using green tea and black tea leaves extracts. Synthesized NPs were characterized using SEM, FTIR, EDX and UV/Vis spectroscopy techniques. Antibacterial activity of NPs was assessed against methicillin- and vancomycin-resistance Staphylococcus aureus strains. Antifungal activity was investigated against Aspergillus flavus and A. parasiticus fungal species. Adsorbent capability with aflatoxin B1 (AFB1 ) was also assessed in solution. Ag-NPs showed superior antibacterial/antifungal activities and reduced the aflatoxins production in comparison to Fe-NPs and Cu-NPs. Adsorption capability of all NPs with AFB1 contamination was found in the order of Fe-NPs > Cu-NPs > Ag-NPs. The equilibrium data showed the favorability of Langmuir isotherm with the adsorption capacity (131–139 ng/mg), Cu-NPs (114–118 ng/mg) and Ag-NPs (110–115 ng/mg). Thermodynamic parameters and kinetic studies revealed that adsorption process is spontaneous, endothermic and followed the pseudo-second order. These results suggest that the synthesized NPs could be effectively utilize as an alternative antibacterial/antifungal agent against diseases caused by multiple drug resistant pathogens. In addition, these metal NPs may be utilize as a possible aflatoxins adsorbent in human food and animal feed such as rice, wheat, maize, red chillies and poultry feed. Highlights: Eco-friendly Fe, Cu and Ag NPs were synthesized using green and black tea leaves extracts. Antimicrobial activities of NPs were assessed against S. aureus and Aspergillus. Ag-NPs showed excellent antibacterial/antifungal activities than Cu-NPs and Fe-NPs. Adsorption capability of NPs with aflatoxin B1 was in the following order Fe > Cu > Ag. Adsorption mechanism of aflatoxin B1 using all nanoparticles was proposed.